Peramalan Penjualan Produk Susu Steril PT XYZ di Pasar Jakarta Tahun 2025 Menggunakan Model ARIMA (Autoregressive Integrated Moving Average): Sales Forecast for PT XYZ’s Sterilized Milk Products in the Jakarta Market for 2025 Using the ARIMA (Autoregressive Integrated Moving Average) Model - Prastio, Akbar Bimo; Widhiono, Imam; Lestari, Sri; Dharmawan, Budi (Journal of Integrated Agribusiness, 2025)
This study examines the sales forecast for PT XYZ’s sterilized milk products, recognizing the critical importance of accurate forecasting in the dynamic and competitive fast-moving consumer goods (FMCG) sector. Reliable forecasts are essential for distributors to optimize demand planning and inventory control. The Autoregressive Integrated Moving Average (ARIMA) model was applied to historical monthly sales data from 16 distributors in the Jakarta market covering the 2022–2024 period. The ARIMA procedure included data collection and visualization, stationarity testing (ADF, ACF, PACF), differencing, model identification, parameter estimation, and optimal model selection. The results reveal monthly sales fluctuations with a clear downward trend toward the end of the observation period, with the ARIMA (1,0,1) model emerging as the best fit. Forecasts for 2025 indicate a continued decline in sales value, underscoring the need for stronger collaboration between PT XYZ and its distributors in promotional planning and inventory management to adapt to market shifts and capitalize on emerging opportunities.